2014
DOI: 10.1016/j.cell.2014.06.003
|View full text |Cite|
|
Sign up to set email alerts
|

Yap1 Activation Enables Bypass of Oncogenic Kras Addiction in Pancreatic Cancer

Abstract: SUMMARY Activating mutations in KRAS are among the most frequent events in diverse human carcinomas and are particularly prominent in human pancreatic ductal adenocarcinoma (PDAC). An inducible KrasG12D-driven mouse model of PDAC has established a critical role for sustained KrasG12D expression in tumor maintenance, providing a model to determine the potential for, and the underlying mechanisms of, KrasG12D–independent PDAC recurrence. Here we show that some tumors undergo spontaneous relapse and are devoid of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
501
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 582 publications
(545 citation statements)
references
References 57 publications
24
501
3
Order By: Relevance
“…In this model, oncogenic Kras extinction permanently eliminates most tumors; however, a subset of tumors can bypass Kras dependency and undergoes spontaneous recurrence (Kapoor et al 2014). Multidimensional genomic, transcriptomic, and proteomic profiling has revealed several distinct mechanisms, including, most prominently, amplification of the Yap1 oncogene of the Hippo pathway (Kapoor et al 2014).…”
Section: Oncogenic Kras Escapersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, oncogenic Kras extinction permanently eliminates most tumors; however, a subset of tumors can bypass Kras dependency and undergoes spontaneous recurrence (Kapoor et al 2014). Multidimensional genomic, transcriptomic, and proteomic profiling has revealed several distinct mechanisms, including, most prominently, amplification of the Yap1 oncogene of the Hippo pathway (Kapoor et al 2014).…”
Section: Oncogenic Kras Escapersmentioning
confidence: 99%
“…In this model, oncogenic Kras extinction permanently eliminates most tumors; however, a subset of tumors can bypass Kras dependency and undergoes spontaneous recurrence (Kapoor et al 2014). Multidimensional genomic, transcriptomic, and proteomic profiling has revealed several distinct mechanisms, including, most prominently, amplification of the Yap1 oncogene of the Hippo pathway (Kapoor et al 2014). Interestingly, YAP1 was also identified in multiple genetic screens as one of the top hits that confer resistance to KRAS suppression or targeted cancer therapy with RAF and MEK inhibitors (Shao et al 2014;Lin et al 2015), further corroborating the role of the YAP1 pathway in driving resistance to targeted therapy.…”
Section: Oncogenic Kras Escapersmentioning
confidence: 99%
“…YAP1 is a transcriptional coactivator in the Hippo signaling pathway (15). Increased YAP1 expression or activity can promote the growth of tumor cells, including human HCC (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that β-catenin-driven cancers require a YAP1 transcriptional complex for survival and tumorigenesis (14). Enforced YAP1 expression can enable tumor maintenance upon Kras G12D extinction in a human pancreatic ductal adenocarcinoma model (15). Moreover, YAP1 amplification has been described as an essential oncogene in various types of human cancers, including human HCC (16).…”
Section: Introductionmentioning
confidence: 99%
“…Other areas where there is obvious potential for engineering input include: novel biosensors and pointof-care diagnostics for early detection of disease via the capture and detection of circulating biomarkers (liquid biopsies) [24][25][26][27]; the use of smart wearable or implantable electrochemical sensors to characterise tumour response to chemotherapy in situ or to monitor disease progression and/or signs of relapse [28,29]; artificial intelligence (AI), such as machine learning to help physicians make better diagnoses and guide treatment decisions while minimising costs [30]; metabolic and proteomic profiling of body fluids for the identification of tumoural areas in situ [31][32][33]; and disease-detecting or disease-fighting nanotechnologies (e.g. DNA nanobots [34], quantum dots [35]) for reporting disease status and selectively delivering drugs to tumour cells whilst minimising systemic side effects [36].…”
mentioning
confidence: 99%